2016
DOI: 10.1149/2.1321608jes
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Oxidation Mechanisms on Perovskite Solid Oxide Fuel Cell Anodes

Abstract: Solid oxide fuel cells with (La,Sr)(Ga,Mg)O3 electrolytes and Sr(Ti0.3Fe0.7)O3 anodes and cathodes yield a power density of 0.6 W/cm2 at 0.7 V at 800°C in air and humidified hydrogen. The polarization resistance values are 0.085 Ω·cm2 for the cathodes and 0.13 Ω·cm2 for the anodes. The cell current-voltage characteristics and the anode resistance dependence on hydrogen partial pressure (pH2) both indicate that adsorption limits the hydrogen oxidation process. A model is developed where dissociative hydrogen ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 43 publications
8
66
2
Order By: Relevance
“…The power law-type dependence, Ri  CH2 n , was obtained with n= -0.45, -0.31, and -0.16 at 450 ˚C, 500 ˚C, and 550 ˚C, respectively. Similar power law dependence of anodic polarization resistance on the H2 partial pressure has been observed in several studies on solid oxide fuel cells 14,24. According to the model Zhu et al developed, a power law exponent of -1 corresponded to dissociative adsorption of H2 as the rate-limiting…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The power law-type dependence, Ri  CH2 n , was obtained with n= -0.45, -0.31, and -0.16 at 450 ˚C, 500 ˚C, and 550 ˚C, respectively. Similar power law dependence of anodic polarization resistance on the H2 partial pressure has been observed in several studies on solid oxide fuel cells 14,24. According to the model Zhu et al developed, a power law exponent of -1 corresponded to dissociative adsorption of H2 as the rate-limiting…”
supporting
confidence: 76%
“…As shown in Figure 10 step, whilst a value of -0.5 corresponded to the charge-transfer reaction limit. 24 If this model also holds for the present case, the much smaller n value obtained here relative to -1 would exclude a significant role of gas diffusion or dissociative adsorption limit.…”
Section: Electrochemical Processesmentioning
confidence: 53%
“…47 closest to the present conditions -750 100 mbar H 2 , and 30 mbar H 2 O. From the electrochemical data of the thin film, the ASR of a porous electrode can be calculated by using a transmission line circuit model 51 and microstructural data from 3D tomography: 47 …”
Section: Resultsmentioning
confidence: 73%
“…It was further shown in Ref. 47 that a catalytic metal on the oxide surface promotes hydrogen dissociative adsorption, with subsequent "spillover" of H atoms from the metal onto the oxide surface. A spillover mechanism can also explain why the 5 nm Ti adhesion layer does not strongly impede the TPB effect.…”
Section: Resultsmentioning
confidence: 99%
“…[83] To address that problem, perovskite oxidesh ave been found to exhibit ah igherp olarization resistance as compared with Ni-based anodes. [84] Hence, ase xcellent candidate anode materials potentially combining the best attributes of all of these materials,N i-based perovskite oxide composites have been reported. Specifically,c lasses of Fe-and Ni-doped LaSrCrO 3 [60] Electrochemical data have shown that the maximum power density and maximum current density performance metrics of af uel cell incorporating these different anodesi ncreased in the order of LSCFe (i.e.,3 60 mW cm À2 and 1000 mA cm À2 ) < LSCNi (i.e.,4 60 mW cm À2 and 1300 mA cm À2 ) < LSCNi-Fe (i.e., 560 mW cm À2 and 1700mAcm À2 ).…”
Section: Solid Oxide Fuel Cells (Sofc): Hydrogen Oxidation Reactionatmentioning
confidence: 99%